Studentsâ Ability and Thinking Profile in Solving Plane Problems by Provision of Scaffolding - Sugiyanti, Sugiyanti; Muhtarom, Muhtarom (Universitas Muhammadiyah Surakarta, 2016)
This study aims to reveal thinking profile and problem solving ability of mathematics department students of Universitas PGRI Semarang in solving plane problem by providing scaffolding. Type of this study is a qualitative research. The selection of research subject is based on studentsâ ability, feedback from lecturers and fluency both in oral or writing. Data collection technique used is Think Aloud Method. The results of the study provide an overview that after being given scaffolding, students with intermediate level of mathematics have characteristics: using the assimilation thinking process in understanding the problem, using assimilation and accommodation in planning to solve the problem. The students with lower level Â of mathematics, they use assimilation thinking process in understanding the problems and planning the settlement whereas they are not able to use accommodation thinking process.Â Studentsâ inability in accommodation thinking process causes they can not make solution planning correctly, solve the given problems and checking the solutions. The study shows the students experienced a lot of thinking process development since they have been able to use all of information for solving the problems. The number of the given scaffolding depends on individuals and the level of studentsâ tinking ability.